A Review of the Literature on Primary Leiomyosarcoma of the Prostate Gland. (12th November 2015) - Venyo, Anthony Kodzo-Grey
Abstract : Primary leiomyosarcoma of the prostate (PLSOP) is rare, with less than 200 cases reported so far. PLSOPs present with lower urinary tract symptoms, haematuria, and perineal pain; may or may not be associated with a history of previous treatment for adenocarcinoma of prostate by means of radiotherapy and or hormonal treatment; may afflict children and adult male. Examination may reveal benign enlarged prostate and hard enlarged mass. PLSOPs may be diagnosed by histological examination findings of spindle-shaped carcinoma cells in prostate specimens. Immunohistochemical staining tends to be positive for vimentin, CD44, smooth muscle actin, and calponin, focally positive for desmin, and at times positive for keratin. They stain negatively for PSA, S-100, CD34, CD117, and cytokeratin. Cytogenetic study on primary leiomyosarcoma of the prostate gland may show clonal chromosomal rearrangement involving Chromosomes 2, 3, 9, 11, and 19. On the whole the prognosis is poor. Surgery with or without chemotherapy would appear to be the mainstay of treatment for PLSOPs that are operable, but generally there is no consensus opinion on the best therapeutic approach. Most cases of PLSOPs are diagnosed in an advanced stage of the disease. A global multicenter trial is required to find therapies that would improve the prognosis.